The influence of emotional intelligence and personal styles of dealing with conflict on strategic decisions - Raed Alharbi; Alhamzah Alnoor (PSU Research Review, 2024)
Purpose – Organizations seek to achieve the best results for their strategic decisions by increasing the effectiveness of the vertical and horizontal interconnection. This leads to an efficient and effective flow of information when making decisions (from the bottom-up) and information related to those decisions when starting to implement them on the ground (from Top-down). Thus, the article aims that, it requires managers at all levels to practice relational leadership skills, the most important of which is dealing with emotions (through emotional intelligence (EI)) and conflicts (through personal styles). Design/methodology/approach – In this paper the views of 324 managers were surveyed in several small and medium-sized companies in Saudi Arabia. The respondents were selected randomly. Findings – A direct positive effect of EI, patterns of cooperation and comprehension to deal with conflict was found on the results of strategic decisions and indirectly through relational leadership. Research limitations/implications – This paper is restricted to the relevant literature on the influence of EI and personal styles of dealing with conflict on strategic decisions. Practical implications – As part of the practical implication and managerial decision, policymakers should note that intelligence directly impacts strategic decisions. Originality/value – This is one of the few studies that focused on the level of EI when choosing managers for organizational units and divisions.